Locating the Kingdom of God: performing sacred boundaries - Wenell, Karen J. ca. 21. Jh. (The Library of New Testament Studies, 2024)
Cover -- Contents -- List of Illustrations -- Acknowledgements -- 1 Introducing the Kingdom of God as Emplaced -- 2 Foundations: The Kingdom as Performative Sacred Space -- 3 Synoptic Building Blocks: The Kingdom as Sacred Space in Texts -- 4 Extensions into Cultural Performance: The Kingdom and the Consumer Realm -- 5 Extensions into Ethical Responsibility: The Kingdom and Obligations to Others -- 6 Future Plans: Environmental and Decolonizing Directions of Travel -- Bibliography -- Index of Subjects and Authors -- Index of References.